Explaining personality pay gaps in the UK - Alita Nandi; Cheti Nicoletti (University of Essex, Institute for Social and Economic Research (ISER), 2009)
Using the British Household Panel Survey we examine how the Big Five personality traits openness to experience, conscientiousness, extroversion, agreeableness, and neuroticism affect wages. We estimate mean and quantile pay gaps between people with low and high levels of each of the Big Five, and decompose these pay gaps in the part explained by differences in workers characteristics and in the residual unexplained part. We find that openness to experience is the most relevant personality trait followed by neuroticism, agreeableness and extroversion. Openness and extroversion are rewarded while agreeableness and neuroticism are penalized.
Keywords: 330